Literatura jako perverzní strategie: Alain Robbe-Grillet - Denis Katsaros (Svět Literatury, 2025)
The perverse imagery was always one of the privileged and declared sources of Alain Robbe-Grillet’s artistic expression. This study tries to find a latent core under the surface of Robbe-Grillet’s sadis tic images, which reside in the splitting of the literary subject: a splitting which these images try to intensify and remove at the same time in their self-contradictory circular movement, whether at the level of the doubles of literary characters or of the author himself. The image conceived as a fetish will be used with regard to Lacanian psychoanalytic theory as a tool for interpreting the structure of Robbe-Grillet’s fiction marked by a paradoxical indifference to the differences and logic of the real world.